KEMANDIRIAN EKONOMI KELOMPOK WANITA NELAYAN MELALUI OLAHAN ABON IKAN TONGKOL DI KELURAHAN BUNGKUTOKO - Abdullah, Sukmawati; Hamzah, Awaluddin; Rosmawati, Rosmawati; Bunyamin, Bunyamin; Purwanti, Rahayu Endah; Batoa, Hartina; Jayadisastra, Yoenita; Dima, Darsilan (Universitas Halu Oleo, 2024)
The marine and fisheries sector is one of the priority regional development programs to realize food sovereignty in supporting various other development sectors. Therefore, the Government continues to boost the maritime and fisheries sector because it has an important role in realizing economic independence, especially in Southeast Sulawesi. In 2023, fisheries production was recorded at 268,000 tons or an increase from the previous number of 253,359 tons in 2022. Bungkotoko Village is one of the coastal areas in Kendari City with the majority of the population working in the fisheries sector, around 29% of the total population, so marine products are source of income for the community. The majority of fishermen in Bungkutoko are men, and the role of female fishermen in economic activities is still minimal. Tuna is one type of fish that is abundant in Bungkutoko waters. However, the price is relatively fluctuating and is easily damaged so it needs to be processed so that its value is more durable and profitable. One of the promising preparations is to make shredded tuna fish. This product diversification aims to meet the diverse and growing tastes of consumers so that there are always alternatives and refreshing menus, in this way market saturation can be overcome. The aim of this service activity is for the women fishermen group to know about innovations in how to process shredded tuna fish with less capital because it does not use coconut milk so that the shelf life can be longer, there will be an increase in the skill/ability of the partner group to manage and develop their business and produce highly competitive products. The implementation method consists of stages: socialization, counseling, training (practice), and evaluation. Through this activity, it is hoped that it can increase household income as an effort to increase the family's economic independence.